THE INFLUENCE OF BUSINESS MANAGEMENT ON INCOME AND THE RISK OF INCOME IN THE BROILER CHICKEN FARMING - Suwarta, Suwarta; Hanafie, Rita (JOURNAL OF SOCIOECONOMICS AND DEVELOPMENT, 2018)
Broiler meat is an important commodity to support national meat production and increase farmer's income. However, the broiler farmers are generally in a weak position in terms of poultry management. They require best management practices for increasing the business volume and income as well. This study aims to study the achievement of broiler farming business management, and the influence of the business management on income and its income in their broiler farms. This research was conducted in Lamongan regency. It used the primary data from selected the broiler farmers. The analysis method used was descriptive approach and multiple regression. The result shows that the achievement of broiler business management comprises planning 67.6%, organizing 65.68%, directing 84.18%, coordination 75.43%, and control 77.58%. The management of broiler business has a positive effect on income but negatively affects the income risk. In addition, the income of broilers is positively influenced by the cage size, experience, and business volume, and conversely, this is negatively affected by seed prices and feed prices. Meanwhile, the income risk of broiler business is positively influenced by seed price and feed price, and contrarily it is negatively influenced by the size of cage and the business volume